2022
DOI: 10.1289/ehp12006
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of Trichloroethylene and Tetrachloroethylene Metabolism to Glutathione Conjugates Using Human, Rat, and Mouse Liver in Vitro Models to Improve Precision in Risk Characterization

Abstract: Background: Both trichloroethylene (TCE) and tetrachloroethylene (PCE) are high-priority chemicals subject to numerous human health risk evaluations by a range of agencies. Metabolism of TCE and PCE determines their ultimate toxicity; important uncertainties exist in quantitative characterization of metabolism to genotoxic moieties through glutathione (GSH) conjugation and species differences therein. Objectives: This study aimed to address these uncertainties using nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
(96 reference statements)
1
3
0
Order By: Relevance
“…In summary, the work by Valdiviezo et al. 12 validated several in vitro liver models, particularly the micropatterned coculture model, and provided metabolism data for GSH conjugation of TCE and PCE that generally agree with those that my colleagues and I reported. 8 , 17 – 21 These new findings thereby provide greater confidence in using these data for physiologically based pharmacokinetic models and human health risk assessment.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…In summary, the work by Valdiviezo et al. 12 validated several in vitro liver models, particularly the micropatterned coculture model, and provided metabolism data for GSH conjugation of TCE and PCE that generally agree with those that my colleagues and I reported. 8 , 17 – 21 These new findings thereby provide greater confidence in using these data for physiologically based pharmacokinetic models and human health risk assessment.…”
supporting
confidence: 75%
“…In a study reported in this issue of Environmental Health Perspectives , Valdiviezo et al. 12 performed new analyses of the metabolism of TCE and PCE by the GSH conjugation pathway. Their goal was to resolve uncertainties in quantitative data for risk assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, how to stably extract primary adipocytes and hepatocytes in NAFL pathological conditions has become an urgent technical difficulty to be solved. The isolation methods of primary hepatocytes and precursor adipocytes included mechanical isolation, simple enzymatic digestion, collagenase digestion [14,15] , etc. In this study, NAFL model was established by feeding SD rats with HFD and optimized in the traditional isolation method.…”
Section: Hepatocyte Oro Staining and Tg Detection Resultsmentioning
confidence: 99%
“…In addition, interspecies variability in the oxidative metabolism of TCE indicates that rodents metabolize TCE more rapidly than humans 40 . Mice even exhibit strain-dependent variability of metabolism in [41][42][43][44] , suggesting that greater doses beyond simple allometric scaling would be necessary in laboratory animals to accurately replicate exposure. Thus, dose conversions of TCE exposure from animal to human and vice versa, are complex, rely on imperfect conversion assumptions, and should be considered in the temporal context of a human lifespan.…”
Section: Discussionmentioning
confidence: 99%